THE LIFE OF DUTCH MISSIONARIES IN EASTERN INDONESIA IN DETENTION CAMPS AT SOUTH SULAWESI (1942-1945) - Cakranegara, Joshua Jolly Sucanta (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This article discussed the life of Dutch missionaries in Eastern Indonesia in detention camps in South Sulawesi during the Japanese occupation period (1942-1945). This was motivated by the political policy of the Japanese Navy as the ruler of the East Indonesia region which tried to eliminate all kinds of Western influence, one of which was through the detention of Catholic missionaries. This article used a historical method based on a literature study. The study result showed that several places in South Sulawesi, such as Makassar, Malino, Kampili, Pare-Pare, Bojo, and Bolong were chosen as the detention camps for Dutch Catholic missionaries in Eastern Indonesia, because they were the central government of the Japanese Navy in Eastern Indonesia. Besides, the poor conditions of the detention camps and prone to armed attacks caused many missionaries die there while being detained in 1942 and 1943. Some of the missionaries who survived were returned to their mission lands from late 1945 to early 1946. At the end, this crucial period had a major impact on the history of the Catholic Church in Indonesia, that was the absence of Dutch missionaries in the mission lands as well as the common active involvements and a few Japanese missionaries in carrying out missions.